A STUDY ON THE QUALITY OF BANKING SERVICE AND ITS ROLE IN ACHIEVING CUSTOMER SATISFACTION, ALONG WITH A STUDY OF A NUMBER OF PRIVATE BANKS - Ali Abudel Qader Ahmed; Mohammed Abdulkareem Ahmed (Scholars Digest Publishing, 2024)
The current study aims to identify the level of quality of banking services provided by some banks. This study is important because it covers one of the topics that comes in the services aspect, providing a database for customers, by providing a customer database and the extent of customer satisfaction with these services that they provide, which led to that These banks have begun to be interested in providing good services, including the level of services that the customer expects is higher than the level of actual services. Therefore, this study has reached a set of recommendations, the most important of which is that the leadership of (successful) banking departments must rely on modern marketing techniques, the most important of which is relationship management. The customer it will help her know information about all her customers and what their needs are and thus the services that suit them will be provided.
Keywords: service quality, customer satisfaction, private banks.